Kyoto and carbon leakage: An empirical analysis of the carbon content of bilateral trade - Rahel Aichele; Gabriel J. Felbermayr (Center for Economic Studies and ifo Institute (CESifo), 2011)
Has the Kyoto Protocol induced carbon leakage? We conduct the first empirical ex-post evaluation of the Protocol. We derive a theoretical gravity equation for the CO2 content of trade, which accounts for intermediate inputs, both domestic and imported. The structure of our new panel database of the carbon content of sectoral bilateral trade flows allows controlling for the endogenous selection of countries into the Kyoto Protocol. Binding commitments under Kyoto have increased committed countries' embodied carbon imports from non-committed countries by around 8% and the emission intensity of their imports by about 3%. Hence, Kyoto has indeed led to leakage.
Keywords: F18; Q54; Q56; 330; carbon leakage; CO2 content of trade; gravity equation; Kyoto Protocol